SAT0224 The role of intensive immunosuppressive therapy in the management of sle-associated pulmonary arterial hypertension: a single-center cohort study. (15th June 2017) - Wang, Q; Zhao, J; Qian, J; Tian, Z; Li, M; Zeng, X
Abstract : Background: Autoimmune and inflammatory mechanisms could play a significant role in the pathogenesis of pulmonary arterial hypertension (PAH), especially in patients with systemic lupus erythematosus (SLE). The effect of immunosuppressive therapy in the treatment of SLE-associated PAH (SLE-PAH) has not been fully investigated in a large cohort previously. Objectives: We aimed to review the clinical outcomes in patients with SLE-PAH cohort treated with intensive immunosuppressive therapy with or without PAH-targeted therapy. Methods: In this single-center cohort study, 126 patients with SLE-PAH were consecutively enrolled between May 2006 through December 2015. All patients were performed right heart catheriazation to confirm the diagnosis of PAH, and all received intensive immunosuppressive therapy including combination of high-dose glucocorticosteroids and immunosuppressants, such as cyclophosphamide, mycophenolate and calcineurin inhibitors. Baseline demographics, clinical features, laboratory findings, hemodynamic measurements and treatment were analyzed. Kaplan-Meier curves and Cox proportional hazards regression analysis were used to evaluate the role of intensive immunosuppressive therapy. Results: Of the 126 SLE-PAH patients, eighty-two (65.1%) patients received PAH-targeted therapy at baseline. Demographic and clinical characteristics were shown in Table 1 . Survival analysis indicated that responders had a better survival than nonresponders in both with and without PAH-targeted therapy groupPatients with a shorter SLE disease duration (p=0.009) and better baseline pulmonary hemodynamics (mean pulmonary arterial pressure, pulmonary vascular resistance and Cardiac index, p<0.001) were more likely to benefit from immunosuppressive therapy (Table 1 ). Conclusions: Intensive immunosuppressive therapy markedly improved the long-term outcomes of SLE patients with PAH, especially in the early stage of PAH. References: Chung L, Liu J, Parsons L, et al. Characterization of connective tissue disease-associated pulmonary arterial hypertension from REVEAL: identifying systemic sclerosis as a unique phenotype. Chest, 2010; 138:1383–94. Shirai Y, Yasuoka H, Okano Y, Takeuchi T, Satoh T and Kuwana M Clinical characteristics and survival of Japanese patients with connective tissue disease and pulmonary arterial hypertension: a single-centre cohort. Rheumatology (Oxford), 2012; 51:1846–54. Kang KY, Jeon CH, Choi SJ, et al. Survival and prognostic factors in patients with connective tissue disease-associated pulmonary hypertension by echocardiography: results from a Korean nationwide registry. Int J Rheum Dis, 2015. Miyamichi-Yamamoto S, Fukumoto Y, Sugimura K, et al. Intensive immunosuppressive therapy improves pulmonary hemodynamics and long-term prognosis in patients with pulmonary arterial hypertension associated with connective tissue disease. Circ J, 2011; 75:2668–74. Price LC, Wort SJ, Perros F, et al. Inflammation in pulmonary arterial hypertension. Chest, 2012; 141:210–21. Disclosure of Interest: None declared